2020
DOI: 10.1101/2020.04.02.021378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Chromatin Architecture Analysis inXenopus tropicalisReveals Conserved Three-Dimensional Folding Principles of Vertebrate Genomes

Abstract: 23Metazoan genomes are folded into 3D structures in interphase nuclei. 24 However, the molecular mechanism remains unknown. Here, we show that 25 topologically associating domains (TADs) form in two waves during Xenopus 26 tropicalis embryogenesis, first at zygotic genome activation and then as the 27 expression of CTCF and Rad21 is elevated. We also found TAD structures 28 continually change for at least three times during development. Surprisingly, 29 the directionality index is preferentially stronger on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 70 publications
(111 reference statements)
4
5
0
Order By: Relevance
“…Accordingly, we show here that CTCF is also required for chromatin structure in zebrafish embryos (Fig. 1), extending these conclusions to vertebrates and in agreement with a recent report showing that CTCF knockdown in Xenopus embryos altered chromatin structure 41 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Accordingly, we show here that CTCF is also required for chromatin structure in zebrafish embryos (Fig. 1), extending these conclusions to vertebrates and in agreement with a recent report showing that CTCF knockdown in Xenopus embryos altered chromatin structure 41 .…”
Section: Discussionsupporting
confidence: 93%
“…1a-d). These data confirmed that CTCF is essential for 3D chromosome organization in zebrafish embryos, as described for other vertebrates including mammals and frogs 5,15,41 . Next, we analyzed A and B compartments in wild-type and ctcf −/− embryos and, although we found a similar distribution of AB compartments, we detected increased AB interactions and decreased compartmentalization strength in the mutants (Extended Data Fig.…”
Section: Ctcf Is Required For Chromatin Organization In Zebrafish Embsupporting
confidence: 87%
See 1 more Smart Citation
“…1a-d). These data confirmed that CTCF is essential for 3D chromosome organization in zebrafish embryos, as described for other vertebrates including mammals and frogs 5,15,43 . Next, we analyzed A and B compartments in wild-type and ctcf -/embryos and, although we found a similar distribution of AB compartments, we detected increased AB interactions and decreased compartmentalization strength in the mutants ( Supplementary Fig.…”
Section: Ctcf Is Required For Chromatin Organization In Zebrafish Embsupporting
confidence: 86%
“…Fourth, although TADs and loops were initially reported to be cell-type invariant [ 11 , 132 ], it has now become clear that cell differentiation is associated with widespread changes to TAD and loop organization [ 133 140 ]. Consistently, mutating RBRs in CTCF only disrupts a subset of loops [ 36 , 37 ] and CTCF binding can be regulated [ 141 , 142 ].…”
Section: Discussionmentioning
confidence: 99%